PENGARUH EDUKASI MELALUI ASUHAN KEPERAWATAN GIGI TERHADAP KEBERSIHAN GIGI DAN MULUT PADA PASIEN PASCA PENCABUTAN GIGI KARENA KARIES - Ni made Yuliana; Hendri Setiawan; Ratnawati Hendari (Jurnal Kesehatan Gigi (Dental Health Journal), 2014)
Background:. Oral hygiene and bad teeth is one of the causes of dental caries, Dental care through nursing education was an effort to improve the knowledge, attitudes, actions to improve one's oral hygiene and mouth. Objective: To analyze the effect of education through dental nursing care of oral hygiene and mouth in patients after tooth extraction because of caries.  Methods: This study uses a true experiment with pre and post test approach in the intervention group and the control group. The research sample using random sampling techniques. Total Samples 46, 23 grouped interventions, 23 grouped control. Measurements were taken before and after intervensi using questioner, Plaque Index (PHP) and OHIS. Data were analyzed using univariate and bivariate using Mann-Whitney Test, Wilcoxon Signed Ranks Test, Chi-quare, Independent Samples Test and Paired Samples Test. Results: There was the influence of dental nursing care through dental education on knowledge, attitude measures, OHI-S and Plaque (PHP) with p value 0.001. Conclusion: Education through dental nursing care can be an alternative or a model of intervention in health centers to improve knowledge, attitudes, actions, oral hygiene and mouth in patients after tooth extraction because of caries.